In vivo study of celery (Apium graveolens L) extract for regenerating pancreatic β-cell - Ismail, Dina Dewi Sartika Lestari; Kristianto, Heri; Setyoadi, Setyoadi; Maydinah, Anissa (Universitas Muhammadiyah Purwokerto, 2024)
Background: The celery plant (Apium graveolens L.) is a widely distributed herbal plant globally known for being a significant source of natural active products, including phenolic compounds and antioxidants demonstrating antidiabetic activity. Previous research findings have indicated the impact of celery leaf extract on reducing blood glucose levels. However, up to now, there is a dearth of research investigating the potential effect of celery leaf extract on the regeneration of pancreatic beta cells in mice with diabetes models.Objective: This study aims to determine the effect of the ethanol extract of celery leaves on the number of pancreatic cells in Streptozotocin (STZ)-induced mice.Method: This research method uses a randomized controlled group posttest only design. Experimental animals were divided into five groups, including a group of experimental animals in a healthy condition, the group with hyperglycemia, hyperglycemia group with celery extract at 200 mg/kg BW, hyperglycemia group with celery extract at 400 mg/kg, and hyperglycemia group with extract celery is 800 mg/kg BW. Termination was performed on day 60 after therapy and pancreas hematoxylin and eosin staining. They are counting the number of cells with a photo slide with 400x magnification in 5 fields of view—statistical analysis using One-Way ANOVA.Results: The study revealed that celery extract could increase the number of pancreatic cells compared to the control group (P<0.002). Notably, the highest increase in pancreatic cell count was observed in the group administered with 400 mg/BW of celery extract.Conclusion: Celery leaf extract effectively increased the number of beta cells in vivo.